Implementation of PET/CT in radiation oncology: a patterns-of-care analysis of the German Society of Nuclear Medicine and the German Society of Radiation Oncology - Wegen, Simone; Nestle, Ursula; Zamboglou, Constantinos; Spohn, Simon Konrad Benedict; Nicolay, Nils; Unterrainer, Lena Maria; Körber, Stefan A.; La Fougère, Christian Jean; Fokas, Emmanouil; Kobe, Carsten Andreas; Eze, Chukwuka; Grosu, Anca-Ligia; et al. (Strahlentherapie und Onkologie, 2024)
The use of positron-emission tomography (PET)/computed tomography (CT) in radiation therapy (RT) has increased. Radiation oncologists (RadOncs) have access to PET/CT with a variety of tracers for different tumor entities and use it for target volume definition. The German Society of Nuclear Medicine (DGN) and the German Society of Radiation Oncology (DEGRO) aimed to identify current patterns of care in order to improve interdisciplinary collaboration.
Online veröffentlicht: 9. August 2024
Gesehen am 26.05.2025